Совершенствование тарифов на ледокольную проводку - Zagorodnikov, Mikhail (Administrativa Consulting, 2025)
In article topical issues of improvement of transport service on the Northern Sea Route are considered. The icebreaking component of a tariff for icebreaking pilotage on the northern sea thoroughfareis revealed. Offers on structure of the expenses offered for inclusion in a tariff are developed.